1979
DOI: 10.1002/bjs.1800660717
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levamisole on postoperative immunosuppression

Abstract: Cell mediated immunity was studied before and after surgery in patients with colorectal cancer. Thymus-derived (T) lymphocytes were enumerated and their non-specific activity was measured by assessing phytohaemagglutinin (PHA)-induced blastogenesis. Specific T lymphocyte activity was measured by leucocyte migration inhibition in response to purified protein derivative of tuberculin (PPD) and autochthonous tumour extract. One group of patients received levamisole postoperatively and the other group consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…That this was not merely an artefact suggested by a small number of hyper-responsive animals is demonstrated by the significant elevation of LT in levamisole-treated animals compared with untreated controls. This confirms in the rat model our findings that levamisole restores postoperative depression in patients with colorectal cancer [19]. However, it was found that in the human situation, lymphokine production was restored more quickly than was LT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That this was not merely an artefact suggested by a small number of hyper-responsive animals is demonstrated by the significant elevation of LT in levamisole-treated animals compared with untreated controls. This confirms in the rat model our findings that levamisole restores postoperative depression in patients with colorectal cancer [19]. However, it was found that in the human situation, lymphokine production was restored more quickly than was LT.…”
Section: Discussionsupporting
confidence: 89%
“…Success with immunotherapy in the treatment of breast cancer [14] and lung cancer [1,11] has led to increased interest in the use of combinations of chemotherapy and immunotherapy. Combination of these forms of treatment with surgery means that a reduction in tumour bulk can be combined with a restoration of immunity depressed by cancer [17] or surgery [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we have studied the use of immunotherapy following surgery for colorectal cancer, when it is well established that there will be depression of immunity [7]. The immunostimulant chosen for these trials was levamisole which is administered orally and it restore cellular immunity which was depressed by Surgery [15]. After commencement of the trial, evidence emerged of a possible detrimental effect on survival associated with levamisole.…”
Section: Fluorouracil and Levamisole Adjuvant Chemotherapymentioning
confidence: 99%
“…Levamisole, an oral antihelminthic drug, is considered an immunoreconstituting agent or an antianergic agent, 5,6,17,21,35,36,53,73,123,128 It restores depressed immune responses to normal, although it does not stimulate them to a level above the norm. 6 Primarily affected are host defense cells that have the capacity to circulate and thus are able to enter the invaded areas of the body to eliminate the invading cells.…”
Section: Levamisolementioning
confidence: 99%